Evaluation of the Effectiveness of Ethanol Extract of (Acalypha indica L.) Leaves as a Treatment for Gastric Ulcers in Male Rattus norvegicus Rats - Suci Wulandari; Hasni Yaturramadhan Harahap; Rinanda Desela Br Tambunan; Basyariah Lubis (Jurnal FARMASIMED (JFM), 2025)
Acalypha indica L., commonly known as Indian copperleaf, is a wild medicinal plant typically found along roadsides and in gardens. Its leaves contain various bioactive compounds, including saponins, flavonoids, alkaloids, and tannins. Traditionally, the plant has been used for its anti-inflammatory, antibacterial, antifungal, and antioxidant properties, which help combat oxidative stress caused by free radicals. This study aimed to evaluate the effectiveness of ethanol extract of Acalypha indica L. leaves in treating gastric ulcers in male Wistar rats (Rattus norvegicus). This research was a true experimental study involving the extraction of Acalypha indica L. leaves using ethanol, preparation of the extract suspension, and induction of gastric ulcers in rats using aspirin at a dose of 800 mg/kg body weight (BW) administered orally. A total of 30 male Rattus norvegicus rats were divided into six groups. Three control groups is Ulcer control, Negative control, Positive control. Three treatment groups receiving ethanol extract of Acalypha indica leaves (EEAIL) at doses of: EEDAA 50 mg/kgBB, EEDAA100 mg/kg BB, EEDAA 200 mg/kgBB. Ulcer induction was carried out daily until surgical examination was performed on days 4, 9, and 14. Macroscopic observations of the stomach were conducted to assess the number of ulcers and ulcer scores. Statistical analysis was performed using one-way ANOVA, followed by Tukey’s post hoc test to determine significant differences between groups. Macroscopic examination showed that the ethanol extract of Acalypha indica leaves (EEAIL) reduced the number of gastric ulcers. Complete healing of ulcers was observed in the positive control group, as well as in the groups receiving EEAIL at 200 mg/kg BW and 100 mg/kg BW, by day 14. In contrast, the 50 mg/kg BW group and the ulcer control group showed no signs of healing by the end of the observation period. The most effective dose was 200 mg/kg BW, demonstrating the highest capacity to reduce the number of gastric ulcers.